Reconsidering Korea's FTA with China in Its Economic Security. (December 2015) - Lee, Manhee
Abstract : This paper explores how to keep a balance between liberalistic and realistic perspectives in Korea's free trade agreement (FTA) with China by analyzing nations' FTA strategies. The United States uses the FTA as a supplementary to fulfill its grand strategy, while China employs it as a way to prevent the emergence of an anti‐China bloc and to reduce its vulnerability. Their strategic thinking marks the FTA as crucial in attaining these non‐economic and economic objectives. Differed FTA strategies pose a task for a higher‐cost economy to take a balanced posture in its FTA with a low‐cost economy. This feature urges Korea to attempt it for the sake of fostering economic prosperity as well as security in its FTA with China. As a way to practice it, Korea should reconsider Japan's and ASEAN's reoriented behaviors in their relations with China. Under growing asymmetrical interdependence, they resort to the alliance with the United States while maximizing economic benefits in trade with China. Korea can also take a balanced posture by increasing economic benefits in its economic relations with China and by consolidating its ties with the United States. Growing Korea–China interdependence increases their opportunity costs of troubles in trade. Not only the costs, but also the Korea–US ties would constrain China to have an incentive to use its economic advantage in managing the power relations with Korea. Another way to practice it is to undertake a hub and participate at more multilateral regimes. Currently, the Trans‐Pacific Partnership would be an alternative. Reshaping resources diplomacy and improving Korea's image from a Chinese perspective could be adopted as supplementary to attaining economic security in the relations with China.